JIHADISM IN SUB-SAHARAN AFRICA: SPECIFIC FEATURES AND THREAT ASSESSMENT - Filijović, Marko; Oddi, Emanuele (Political Review, 2023)
This paper analyzes the activities of jihadists in the region commonly referred to as the “Black Continent”. The authors provide an analysis of the development of jihadist ideology across the world, followed by a closer examination of its specific manifestations in sub-Saharan Africa. This research study utilized a model originally developed by Geoffrey Predmore in 2011 to analyze the insurgency in the North Caucasus. It includes three key aspects that theorists have identified as necessary for the success of the insurgency: the level of will of the actors involved in achieving the envisioned goals; choosing the strategy of the actors involved; and the extent of external support to the actors involved. The research was based on a content analysis methodology, utilizing a diverse range of reliable data sources, including official reports from international organizations, scientific publications, and newspaper articles. The authors concluded that holy warriors in sub-Saharan Africa possess a strong determination to achieve their goals at the local level. However, this willpower tends to decrease when it comes to global ambitions. When examining their strategy, it becomes evident that they have adopted a primarily indirect approach. Finally, in the context of external support to African jihadist groups, it has been observed that such support does exist. The basic assumption that sub-Saharan jihadists pose a distinct threat to internationally recognized countries in the region, and that they could potentially establish an entity similar to the Islamic State in sub-Saharan Africa, has been partially confirmed. Although they possess a strong will, an elaborate strategy, and specific external support for achieving local goals, it is unlikely that they will be able to constitute something like a caliphate in the near future.